2019
DOI: 10.1155/2019/8958069
|View full text |Cite
|
Sign up to set email alerts
|

Association between Early Acute Respiratory Distress Syndrome after Living-Donor Liver Transplantation and Perioperative Serum Biomarkers: The Role of Club Cell Protein 16

Abstract: Background. Acute respiratory distress syndrome (ARDS) after living-donor liver transplantation (LDLT) is not uncommon, but it lacks the biomarkers for early detection. Club cell protein 16 (CC16), high-motility group box 1 protein (HMGB1), interleukin-1β (IL-1β), and IL-10 have been reported as relevant to the development of ARDS. However, they have not been investigated during LDLT. Methods. Seventy-three consecutive recipients undergoing LDLT were enrolled and received the same perioperative care plan. Peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…According to previous studies, postoperative plasma levels of CC–16 in patients undergoing abdominal surgery was 17.8 ng mL −1 , the standard deviation was 9.4. 5 , 20 Assuming that intravenous infusion of lidocaine can reduce CC-16 by 30%, 53 patients in each group can provide 80% power with a significance level of 0.05. We planned to recruit 62 patients in each group to compensate for 15% dropouts.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, postoperative plasma levels of CC–16 in patients undergoing abdominal surgery was 17.8 ng mL −1 , the standard deviation was 9.4. 5 , 20 Assuming that intravenous infusion of lidocaine can reduce CC-16 by 30%, 53 patients in each group can provide 80% power with a significance level of 0.05. We planned to recruit 62 patients in each group to compensate for 15% dropouts.…”
Section: Methodsmentioning
confidence: 99%
“… 21 In addition, older age was associated with a higher risk of PPCs and poor survival rates since they are at an increased risk of comorbid conditions. 22 Congestive heart failure, a diagnosis of chronic obstructive pulmonary disease, an ASA score of II or higher, or chronic liver disease were independent risk factors for PPCs. 5 , 23–25 Kaw et al showed that patients with obstructive sleep apnoea have a two-fold increase in the risk of developing acute respiratory failure after non-cardiac surgery.…”
Section: Discussionmentioning
confidence: 94%
“…8 Acho et al retrospectively analyzed 279 patients with LT, which revealed that immediate postoperative extubation could decrease pulmonary complications in LT patients. 9 Several biomarkers can be used for prognoses, such as Club Cell Protein 16 (CC16) level and connexin43 (Cx43) function before transplantation, which are related to the occurrence of early ARDS following LT. 10,11 However, no risk factors have been identified that can predict pulmonary complications in LT patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the participants in these studies had a variety of risk factors, making predicting pulmonary complications in actual practice problematic. At present, most studies on biomarkers require specific biological samples for patients, such as bronchoalveolar lavage fluid and lung tissues, which increases the difficulty of prediction, and the results may still require the integration of other clinical data 10,11,13,14 . Therefore, a simple, low‐cost, and highly available prediction method should be proposed to allow for the prediction of lung complications in LT patients more practical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation